Laccaridione C, a Bioactive Polyketide from the Fungus Montagnula sp. - Almeida, Celso; Mackenzie, Thomas Andrew; González-Menéndez, Víctor; de Pedro, Nuria; Pérez-Victoria, Ignacio; Crespo, Gloria; Martín, Jesús; Genilloud, Olga; Vicente, Francisca; Cautain, Bastien; Reyes, Fernando (Planta Medica International Open, 2019)
The new polyketide laccaridione C (1) was obtained by bioassay-guided isolation of organic extracts of the fungal strain CF-223743, isolated from dung collected in a forest of Grand Comoros Island. Its structure was established using spectroscopic methods, namely HRMS and 1D and 2D NMR. The new compound was tested against seven cancer cell lines, evidencing effective activity against melanoma (A2058) with an IC50 of 13.2 µM, and an increased activity against breast cancer (MCF-7) with an IC50 of 3.7 µM. The strain CF-223743 was taxonomically identified as Montagnula sp. based on ITS/28S analysis
Keywords: cytotoxicity; melanoma; bioassay-guided fractionation; laccaridiones; fungal natural products; Montagnula sp.; structural elucidation